Effect of crushable blockouts on a full-scale guardrail system. Issue 1 (2nd January 2017) - Sassi, Sadok; Sassi, Abdelmonaam; Ghrib, Faouzi
ABSTRACT: Since the performance of the guardrail system depends in part on the compatibility of vehicle-to-roadside hardware, it is important to improve the interaction of the vehicle with the guardrail system by adding more compliance to the guardrail system. In this paper, a finite-element baseline model of a guardrail system consisting of a light truck (2000 kg) travelling at 100 km/h and striking a guardrail was developed in accordance with the NCHRP Report 350 guidelines for Test Level 3 safety performance. The model was validated through comparison to a full-scale test conducted by the Texas Transportation Institute. In order for the guardrail system to absorb more energy and offer better stability to the vehicle, a rigid wooden blockout was replaced by a new crushable blockout design that was evaluated at the component level. The new blockout was formed by three crash cans and triggered at the corner, then was implemented in the full-scale model. The results of the analysis indicate that the both models satisfy the requirements of NCHRP Report 350 for the Test 3-11 conditions and show that the crushable blockout offers better vehicle stability in terms of roll angle and vehicle deceleration.